Virtual Environment of an Industrial Process for Learning and Teaching - Cueva, Carlos (2022)
Laboratory stations or modules are essential for the teaching-learning process, not having physical laboratories is a limitation for the educational and training process of future professionals. The use of virtual environments allows students to relate to these processes and replace the need to use a physical module partially or to complement their learning. The virtual environment has an interface like a video game, making students are attracted to the use of these tools; These virtual processes, like the real ones, are suitable for the immersion, inclusion, and subsequent evaluation of control techniques. With the use of the Unity 3D graphic engine, the typical laboratory pressure process is virtualized and through simple and advanced control strategies implemented in the Matlab software, it can be controlled with bilateral communication by shared memories.